Neglected Bilateral Herpetic Stromal Keratitis: A Case Report - Islami, Restiana Hilda; Zuhria, Ismi (Indonesian Journal of Global Health Research, 2025)
Herpes simplex virus (HSV) is a DNA virus with a common predilection of mouth, genitalia and eye. HSK can be classified as either necrotizing or non-necrotizing. HSK is primarily diagnosed clinically. It is often treated with a mix of antiviral drugs and local immunosuppressive therapy. The aim is to minimize local symptoms, inflammation, and scar formation.Case description: A 36-year-old female visited the ophthalmology outpatient clinic at Dr. Soetomo General Academic Hospital with a chief complaint of blurry on her both eyes since 8 months ago. She claimed had vesicles in her face and body about 1 years ago. The patient was diagnosed with non necrotizing herpetic stromal keratitis both eyes and complicated cataract in right eye. She had given Acyclovir 400 mg oral; acyclovir 3% eye ointment, prednisolone acetate eye drop,and artificial tears non preservative.Conclusion: Early diagnosis and adequate therapy of HSK are key to avoid complications. Successful treatment reduces disease duration, prevents progressive corneal scaring and reduces risk of further recurrences.